Optical to UV spectra and birefringence of SiO2 and TiO 2: First-principles calculations with excitonic effects - Lawler, H. M. (2008)
A first-principles approach is presented for calculations of optical, ultraviolet spectra including excitonic effects. The approach is based on Bethe-Salpeter equation calculations using the NBSE code combined with ground-state density-functional theory calculations from the electronic structure code ABINIT. Test calculations for bulk Si are presented, and the approach is illustrated with calculations of the optical spectra and birefringence of alpha-phase SiO2 and the rutile and anatase phases of TiO2. An interpretation of the strong birefringence in TiO2 is presented.